Compliance mechanism under Aarhus Convention - effective legal instrument for enforcement of international environmental law - Osleja, Marta (Riga Graduate School of Law, 2020)
United Nations Economic Commission for Europe Convention on Access to Information, Public Participation in Decision-making and Access to Justice in Environmental Matters Convention on Access to Information, Public Participation in Decision-Making and Access to Justice in Environmental Matters (Aarhus Convention) is first and unique international legal instrument which consists of strictly procedural provisions in environmental matters. The institutional structure of Aarhus Convention consists of a particular subsidiary body, namely Compliance Committee, responsible to assess submissions of civil society regarding failure to comply with treaty provisions. Although Compliance Committee issues unbinding findings and recommendations of the Parties to international legal instrument, currently the quasi-judicial practice of Compliance Committee has gained recognition beyond scope of application of Aarhus Convention in a broader transboundary context. In this thesis the influence of compliance mechanism under Aarhus Convention will be studied. The most important factors which enables efficient implementation and application of environmental participatory rights within the framework of Aarhus Convention and relevant framework of EU law will be determined and analysed.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Environmental law